Sports medicine prevention, assessment, management, and rehabilitation of athletic injuries - Irvin, Richard (Allyn & Bacon, 1998)
Acclaimed for its accuracy and comprehensive style, Sports Medicine has been a favorite in the field for years. The second edition of this text continues this tradition while reflecting the latest trends in the field. Designed to provide an understanding of the injury process, this contemporary volume includes coverage on the subjects of prevention, assessment, first aid, treatment and rehabilitation of sports-related injuries. It provides both students and clinicians with an invaluable reference on the anatomy, pathology, short-term care and long-term care of injuries. This text meets the requirements of the National Athletic Trainers' Association